Find the equation of tangent to the curve x2 + y2 = 5, where the tangent is parallel to the line 2x – y + 1 = 0 - Mathematics and Statistics

Advertisements
Advertisements
Sum

Find the equation of tangent to the curve x2 + y2 = 5, where the tangent is parallel to the line 2x – y + 1 = 0

Advertisements

Solution

Equation of the curve is x2 + y2 = 5   ......(i)

Equation of the line is 2x – y + 1 = 0  ......(ii)

Differentiating (i) w.r.t. x, we get

`2x + 2y ("d"y)/("d"x)` = 0

∴ `("d"y)/("d"x) = (-2x)/(2y) = -x/y`

Let (x1, y1) be any point on the curve.

∴ Slope of the tangent at (x1, y1)

= `(("d"y)/("d"x))_((x_1,  y_1)`

= `-(x_1)/(y_1)`

Slope of the line 2x – y + 1 = `(-2)/(-1)` = 2

Tangent at (x1, y1) is parallel to the line (ii) and hence their slopes are equal.

∴ `-(x_1)/(y_1)` = 2

∴ x1 + 2y1 = 0    ......(iii)

From (i), we get

y2 = 5 – x2

∴ y = `sqrt(5 - x^2)`

∴ `("d"y)/("d"x) = 1/(2sqrt(5 - x^2)) (0 - 2x)`

= `(-x)/sqrt(5 - x^2)`

∴ `(("d"y)/("d"x))_((x_1,  y_1)` = `(-x_1)/sqrt(5 - (x_1)^2)`

= slope of the tangent at (x1, y1)

∴ `(-x_1)/sqrt(5 - (x_1)^2` = 2

Squaring on both sides, we get

∴ `(x_1)^2/(5 - (x_1)^2` = 4

∴ (x1)2 = 20 – 4(x1)2

∴ 5(x1)= 20

∴ (x1)= 4

∴ x1 = ± 2

From (iii), when x1 = 2, then 2 + 2y1 = 0

∴ y1 = – 1

and when x1 = – 2, then – 2 + 2y1 = 0

∴ y1 = 1

Thus, (x1, y1) = (2, – 1) or (– 2, 1)

Now, equations of the tangents are

y + 1 = 2(x – 2) and y – 1 = 2(x + 2)

i.e., 2x –  y –  5 = 0 and 2x –  y + 5 = 0

  Is there an error in this question or solution?
Chapter 1.4: Applications of Derivatives - Q.5

RELATED QUESTIONS

Find the derivative of the following function from first principle.

x3 – 27


Find the derivative of the following function from first principle.

(x – 1) (x – 2)


Find the derivative of the following function from first principle.

`1/x^2`


Find the derivative of the following function from first principle.

`(x+1)/(x -1)`


Find the derivative of the following function from first principle:

−x


Find the derivative of the following function from first principle:

(–x)–1


Find the derivative of the following function from first principle: 

sin (x + 1)


Find the derivative of the following function from first principle: 

`cos (x - pi/8)`


Find the equation of tangent and normal to the curve at the given points on it.

y = 3x2 - x + 1 at (1, 3)


Find the equation of tangent and normal to the curve at the given points on it.

x2 + y2 + xy = 3 at (1, 1)


Find the equations of tangent and normal to the curve y = x2 + 5 where the tangent is parallel to the line 4x − y + 1 = 0.


Find the equations of tangent and normal to the curve y = 3x2 - 3x - 5 where the tangent is parallel to the line 3x − y + 1 = 0.


Choose the correct alternative.

The equation of tangent to the curve y = x2 + 4x + 1 at (-1, -2) is 


Choose the correct alternative.

The equation of tangent to the curve x2 + y2 = 5 where the tangent is parallel to the line 2x – y + 1 = 0 are


Choose the correct alternative.

If 0 < η < 1, then demand is


Choose the correct alternative.

If f(x) = 3x3 - 9x2 - 27x + 15 then


Fill in the blank:

The slope of tangent at any point (a, b) is called as _______.


Fill in the blank:

If f(x) = x - 3x2 + 3x - 100, x ∈ R then f''(x) is ______


Fill in the blank:

If f(x) = `7/"x" - 3`, x ∈ R x ≠ 0 then f ''(x) is ______


State whether the following statement is True or False:

x + 10y + 21 = 0 is the equation of normal to the curve y = 3x2 + 4x - 5 at (1, 2).


Find the equation of tangent and normal to the following curve.

y = x3 - x2 - 1 at the point whose abscissa is -2.


Find the equation of normal to the curve y = `sqrt(x - 3)` which is perpendicular to the line 6x + 3y – 4 = 0.


The slope of the tangent to the curve y = x3 – x2 – 1 at the point whose abscissa is – 2, is ______.


Choose the correct alternative:

Slope of the normal to the curve 2x2 + 3y2 = 5 at the point (1, 1) on it is 


The slope of the tangent to the curve x = `1/"t"`, y = `"t" - 1/"t"`, at t = 2 is ______


State whether the following statement is True or False:

The equation of tangent to the curve y = x2 + 4x + 1 at (– 1, – 2) is 2x – y = 0 


Find the equations of tangent and normal to the curve y = 3x2 – x + 1 at the point (1, 3) on it


Find the equation of tangent to the curve y = x2 + 4x at the point whose ordinate is – 3


Slope of the tangent to the curve y = 6 – x2 at (2, 2) is ______.


Find the equation of tangent and normal to the curve y = x2 + 5 where the tangent is parallel to the line 4x – y + 1 = 0.


Find the equations of tangent and normal to the curve y = 6 - x2 where the normal is parallel to the line x - 4y + 3 = 0


Share
Notifications



      Forgot password?
Use app×